Nigeria : Publication of Financial Sector Assessment Program Documentation -- Detailed Assessment of Compliance of the Basel Core Priciples for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2013)
The assessment of the implementation of the Basel Core Principles (BCP) was conducted for effective banking supervision in Nigeria. The assessment team reviewed the legal framework for banking supervision and held extensive discussions with the staff of the Central Bank of Nigeria (CBN) and the Nigeria Deposit Insurance Corporation (NDIC). It is assessed that Nigeria has recorded significant improvement in its level of compliance with the BCPs, which is attributed to the enhancement of the supervisory capacity of Nigerian banking system supervisors.